Everybody's Doing It: Short Volatility Strategies and Shadow Financial Insurers. Issue 2 (1st April 2018) - Bhansali, Vineer; Harris, Larry
Abstract : The extraordinary growth of short volatility strategies creates risks that may trigger a serious market crash. A low-yield, low-volatility environment has drawn various market participants into essentially similar short volatility-contingent strategies with a common nonlinear risk factor. We discuss these strategies, their commonalities, and the generally unrecognized risks that they would pose if everyone were to unwind simultaneously. Volatility-selling investors essentially provide "shadow financial insurance." Investors and regulators would benefit from preparing for large, self-reinforcing technical unwinds that may occur when/if central banks change policy or macro or political events affect investor confidence. We also discuss potential mechanisms that might provide stabilization against largely adverse financial outcomes. Abstract : Disclosure: The views expressed in this article are those of the authors and do not necessarily reflect the views of LongTail Alpha, LLC; the USC Marshall School of Business; or Interactive Brokers. Further information appears at the end of this article. Editor's Note Submitted 15 November 2017 Accepted 14 February 2018 by Stephen J. Brown LongTail Alpha, LLC, is an SEC-registered investment adviser and a Commodity Futures Trading Commission registered commodity trading adviser and commodity pool operator. The reader should not treat any opinion expressed by Dr. Bhansali as investment advice or as a recommendation to make an investment in any particular investment strategy or product. Many of Interactive Brokers' brokerage clients actively trade volatility products. Professor Harris undertook this project independently of his relationship with Interactive Brokers. He received no compensation for his participation from any entity.